Sample depth, magnetic susceptibility, elemental and sulphur isotope geochemistry for bulk sediments from core RKB 5260 in Lake Pannon - Lin, Zhiyong (PANGAEA, 2023)
The Miocene to Pliocene Lake Pannon was the largest European lake but its methane emission remains unclear in the history. In 2014, serveal boreholes was drilled in the Vienna Basin during the planning phase of subway constructions. Detailed information of drilling processes and cores were described in Harzhauser et al., (2018, doi:10.17738/ajes.2018.0003). Harzhauser et al., (2018) reported abundant tubular pyrite aggregates from Lake Pannon sediments in core RKB5260, which record brackish early lake conditions at ~11.3 Ma. However, the origian of these tubular pyrite aggregates were not clear. In order to evaluate sulphur and carbon cycling in Lake Pannon, we present geochemical, mineralogical, and magnetic evidence to assess the origin of the pyrite aggregates and to test for sulphate-driven anaerobic oxidation of methane signals in the lake sediments. The data presents the magnetic susceptibility, elemental geochemistry (Al, Fe, Ca, Mn, Ba, Mo, P, Ti, K, and Zr contents, and three reactive iron pools, TS, TIC, TOC, chromium reducible sulphur contents) and sulphur isotopic compositions for bulk sediments, as well as SIMS sulphur isotopic compositions of authigenic pyrite from core RKB 5260 in Lake Pannon from the Vienna Basin. The experiment and analyze details were described Lin et al., (2023, doi.org/10.1038/s43247-023-00879-2).
Keywords: Anaerobic Oxidation of Methane; Lake Pannon; Sediment Geochemistry; Sulphur Isotope